An interface stabilized perovskite solar cell with high stabilized efficiency and low voltage loss. Issue 7 (1st July 2019) - Yoo, Jason J.; Wieghold, Sarah; Sponseller, Melany C.; Chua, Matthew R.; Bertram, Sophie N.; Hartono, Noor Titan Putri; Tresback, Jason S.; Hansen, Eric C.; Correa-Baena, Juan-Pablo; Bulović, Vladimir; Buonassisi, Tonio; Shin, Seong Sik; et al.
Abstract : Newly developed passivation strategy results in unprecedented perovskite optoelectronic device performances. Abstract : Stabilization of the crystal phase of inorganic/organic lead halide perovskites is critical for their high performance optoelectronic devices. However, due to the highly ionic nature of perovskite crystals, even phase stabilized polycrystalline perovskites can undergo undesirable phase transitions when exposed to a destabilizing environment. While various surface passivating agents have been developed to improve the device performance of perovskite solar cells, conventional deposition methods using a protic polar solvent, mainly isopropyl alcohol (IPA), results in a destabilization of the underlying perovskite layer and an undesirable degradation of device properties. We demonstrate the hidden role of IPA in surface treatments and develop a strategy in which the passivating agent is deposited without destabilizing the high quality perovskite underlayer. This strategy maximizes and stabilizes device performance by suppressing the formation of the perovskite δ-phase and amorphous phase during surface treatment, which is observed using conventional methods. Our strategy also effectively passivates surface and grain boundary defects, minimizing non-radiative recombination sites, and preventing carrier quenching at the perovskite interface. This results in an open-circuit-voltage loss of only ∼340 mV, a champion device with a power conversion efficiency of 23.4% from a reverse current–voltage scan, a device with a record certified stabilized PCE of 22.6%, and enhanced operational stability. In addition, our perovskite solar cell exhibits an electroluminescence external quantum efficiency up to 8.9%.